2006
DOI: 10.1111/j.1525-1497.2006.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in achievement of cholesterol treatment goals

Abstract: The frequency of treatment success in dyslipidemia management was significantly lower in AA than NHW patients. Additional research is needed to elucidate reasons for this disparity and to evaluate strategies for improving goal achievement among AA patients receiving therapy for dyslipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These findings are consistent with prior studies that have reported Blacks with hyperlipidemia are less likely to use statins, and Blacks are also less likely to achieve their goal cholesterol level. [12][13][14] The reasons for Blacks having more than twice the proportion of Whites to neither be on a cholesterol lowering medication nor at their goal LDL are likely similar to the reasons stated for hypertension. However, with statins, side effects are also likely contributing to racial differences.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with prior studies that have reported Blacks with hyperlipidemia are less likely to use statins, and Blacks are also less likely to achieve their goal cholesterol level. [12][13][14] The reasons for Blacks having more than twice the proportion of Whites to neither be on a cholesterol lowering medication nor at their goal LDL are likely similar to the reasons stated for hypertension. However, with statins, side effects are also likely contributing to racial differences.…”
Section: Discussionmentioning
confidence: 93%
“…8,9 Similar results have been reported for hyperlipidemia, where Blacks are less likely to receive pharmacologic treatment and less likely to reach goal cholesterol levels. [10][11][12][13][14] Stroke survivors are at increased risk of suffering a second stroke. 15…”
Section: Introductionmentioning
confidence: 99%
“…The different efficacy among regions might result from the difference in race. Studies have reported variations in responses to statin therapy among races [ 21 , 22 ]. It is possible that the relatively greater racial diversity in North America result in a wide confidence interval in the North America group.…”
Section: Discussionmentioning
confidence: 99%
“…They found that statin use was less protective of PD in North America than in other geographies, which is something that may account for some of the conjecture and mixed results that had been published previously. Furthermore, and adding to this complexity in terms of confounding interpretation of statin use in the context of PD epidemiology, Clark et al [ 191 ] found that the frequency of treatment success in dyslipidemia management was significantly lower in African American patients in the USA than in non-Hispanic white patients, while Yood at al [ 192 ] found that African American patients initiating statin therapy are less likely to achieve LDL goals, even after controlling for adherence differences and other factors, and suggested that this group may require different pharmacologic management.…”
Section: Epidemiological Studies On the Use Of Statins And The Risk Omentioning
confidence: 99%